Phytochemical studies, thin layer chromatography and gc-ms profiling of olea europaea twig extract / Muhammad Nur Syahir Che Johan - Che Johan, Muhammad Nur Syahir (Faculty of Applied Sciences, 2017)
This study was carried out to investigated the phytochemical analysis and determine the compounds in extraction twig of Olea europaea. The compounds perform were found out to be alkaloids and saponins by using screening process while all the compounds were presence except terpenoids by using TLC process in ethanol extract. In ethyl acetate extract, all the compounds were absence by using screening process while TLC process only flavonoids and terpenoids were appeared. For the hexane extract, only terpenoids was giving positive result by using screening process but from the TLC result, all the compounds were presence by giving positive result. For determining the compounds in extraction twig of Olea europaea by using GC-MS, two solvents had been used namely hexane and petroleum ether. For the result indicated that petroleum ether extracts show more compounds than hexane extracts which 5 compounds were presences.